Evaluating the Impact of Evidence-Based Clinical Practice Guidelines on Patient Outcomes in Primary Care - Perty Adtdy; Kerty Ardy (Yayasan Adra Karima Hubbi, 2025)
Background: The utilization of Evidence-Based Clinical Practice Guidelines (EBCPGs) in primary care has been advocated to enhance patient outcomes by providing standardized, high-quality care. Despite widespread promotion, there is a need for empirical evidence evaluating their actual impact on patient outcomes. Objective: This study aims to evaluate the impact of implementing EBCPGs on patient outcomes in primary care settings, focusing on common chronic conditions such as diabetes, hypertension, and asthma. Methods: A systematic review and meta-analysis were conducted, analyzing data from randomized controlled trials (RCTs) and observational studies published between 2000 and 2023. Studies included in the review examined the implementation of EBCPGs in primary care and reported on patient outcomes such as disease control, hospitalization rates, and patient satisfaction. Data extraction and quality assessment were performed independently by two reviewers. Statistical analyses were conducted using a random-effects model to calculate pooled effect sizes. Results: A total of 30 studies met the inclusion criteria, encompassing 15 RCTs and 15 observational studies. The pooled analysis revealed that the implementation of EBCPGs significantly improved disease control outcomes, with a moderate effect size (Hedges' g = 0.45, 95% CI: 0.30 to 0.60). Hospitalization rates for chronic conditions decreased by 20% (RR = 0.80, 95% CI: 0.72 to 0.89), and patient satisfaction scores improved significantly (mean difference = 0.25, 95% CI: 0.10 to 0.40). Conclusion: The implementation of EBCPGs in primary care settings is associated with improved patient outcomes, particularly in terms of disease control, reduced hospitalization rates, and enhanced patient satisfaction. These findings support the continued promotion and integration of EBCPGs in primary care practice to achieve better health outcomes.